2018
DOI: 10.1530/ec-18-0021
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of insulin resistance assessment in polycystic ovary syndrome

Abstract: BackgroundThough insulin resistance (IR) is common in polycystic ovary syndrome (PCOS), there is no agreement as to what surrogate method of assessment of IR is most reliable.Subjects and methodsIn 478 women with PCOS, we compared methods based on fasting insulin and either fasting glucose (HOMA-IR and QUICKI) or triglycerides (McAuley Index) with IR indices derived from glucose and insulin during OGTT (Belfiore, Matsuda and Stumvoll indices).ResultsThere was a strong correlation between IR indices derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…In our previous study [28], we reported a significant but rather moderate correlation between fasting and OGTT-derived IR indices in women with PCOS, and now we have also demonstrated the same phenomenon for 1 st -trimester pregnant women (Table 3). Hence, in our opinion, with the multitude of mathematical models, there is no universal "gold standard" for the assessment of insulin sensitivity derived from surrogate markers of insulin resistance.…”
Section: Discussionsupporting
confidence: 83%
“…In our previous study [28], we reported a significant but rather moderate correlation between fasting and OGTT-derived IR indices in women with PCOS, and now we have also demonstrated the same phenomenon for 1 st -trimester pregnant women (Table 3). Hence, in our opinion, with the multitude of mathematical models, there is no universal "gold standard" for the assessment of insulin sensitivity derived from surrogate markers of insulin resistance.…”
Section: Discussionsupporting
confidence: 83%
“…For obstetric reasons it was, however, not possible to ensure identical condition for each delivery. There are also several methods to assess insulin resistance 39 , apart from the C-peptide-glucose product that we have employed in our study, but they were not validated for infants, so the choice of "the best" method for the time of delivery is debatable and inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly in our study there was also no significant increase in insulin resistance indices, despite increasing androgenaemia. Detailed information on aspects related to assessment of insulin resistance in our PCOS subjects has been already presented [28].…”
Section: Discussionmentioning
confidence: 99%